Exploring the role of cultural capital in Family-School relationships and connections: A case study of an Irish Postprimary school - NÍ DHUINN, MELANIE (Trinity College Dublin. School of Education. Discipline of Education, 2018)
There are many sociological arguments that have dominated and suffused the notion of family influence and the effect of family structures on children's educational and occupational success. It has been generally recognised that families are critical in promoting educational attainment among children and are pivotal actors in the development of children's cognitive, emotional and social development. Ethnographers have frequently documented the impact of family socioeconomic status on educational outcomes. From an Irish perspective however, emphases within the literature have focused on educational failure and family disadvantage, parental involvement and school effectiveness and exploration of the gendered, classed and "raced" nature of parental involvement. The Irish Education System is both a complex and deeply rooted one where education has always been valued in Irish society. Drawing on Bourdieu's work on cultural capital and with reference to the Post Primary Longitudinal study (PPLS) conducted by the ESRI and the Growing Up in Ireland (GUI) studies this thesis endeavours to examine and explore the cultural elements of Irish families and how these cultural elements impact on education and schooling in Ireland. The research also investigates how various forms of capital coexist and are exchanged within different fields identified in the study. Bourdieu alludes to the production of "habitus" whereby a system of dispositions such as aspirations arbitrates between structures and practice. Bourdieu describes an inculcation effect exerted directly by families and schools on adolescents or by student's individual social backgrounds, but he also proposes a second effect arising from individual?s predispositions such as the accumulation of academic capital which may cause them to resist the forces of the field with their specific inertia that is, their properties, which may exist in the embodied form, as dispositions or in objectified form in goods, qualifications, etc.? Evidence within the literature indicates that students with more "valuable" cultural capital attain greater educational outcomes that their otherwise comparable peers with less "valuable" cultural capital. These theoretical arguments prompted the researcher to construct a case study model to examine and evaluate the influences of cultural capital on students' educational outcomes while attempting to advance the description of the process whereby cultural resources may or may not convert favourably into educational advantages. Data was generated through a mixed methods approach combining both qualitative and quantitative analysis from a cohort of families (parents and post-primary students), staff and management from a coeducational secondary school in the South of Ireland. Five primary data sets were constructed in the study; data through a questionnaire to parents; data generated through a number of focus group with post-primary students; questionnaire and semi-structured interviews with teaching staff and school management and visual data both researcher generated and student generated. The research employed a variety of methodological instruments to elicit both qualitative and quantitative data which were utilised to describe the many family and school cultures that pervade the social context of families and schooling in Ireland while affording an opportunity to investigate the sometimes jarred but interdependent social context in which these cultures exist. Informed by methodological literature that indicates that qualitative methods that rely on selfreporting of thoughts, feelings and experiences of beliefs face the dilemma that internal states are known only by the individual whose prerogative it is whether or not to share them with others and also the fact that such methods of data collection are embedded in social contexts and subject to social manipulation the researcher undertook to consolidate and triangulate the data. Triangulation was ensured through the inclusion of various methodological layers including the construction of visual methodology to enhance and develop the primary data collected through questionnaires to families, focus groups with post primary students and semi-structured interviews with teachers and school management. Taking an empirical approach to the collection of visual data the researcher gathered a combination of researcher generated and participant generated images that were used to further analyse and explore the research question. The research utilised a diverse analysis of data to describe the jagged interface between family cultures and school cultures by foregrounding the data generated through the focus group interviews with the adolescent students which is contextualized by the backdrop of parent, teacher, school staff and school management data. The researcher has prioritized the evidence generated in the student focus groups and extrapolated key thematic findings from the focus groups. Cross tabulations of student focus group data and of data generated through questionnaires, semi-structured interviews and visual constructions are woven throughout the analysis integrating both a vertical and horizontal motif that reveals convergences and divergences between data sets. Contours between numerical and non-numerical data are traversed in order to facilitate analysis of qualitative and quantitative data in response to the research question. The integration of questionnaire data into the thematic analysis of qualitative data reveals findings that supports ethnographic evidence specifically related to the role of families and the promotion of positive educational outcomes. The findings also support a small selection of the Bourdieu theoretical dispositions in relation to the production of habitus and the accumulation of valuable cultural capital and associated positive educational outcomes while rejecting other aspects of the concepts of capital as espoused by various theorists referred to within the theoretical framework. The study is an educational study conducted through the medium of a sociological lens and presents a contemporary description of the complex and contested nature of the cultural capital interface between families and schools in Ireland.
APPROVED
Keywords: Education